Perbedaan Metode Video Tutorial Dan Simulasi Dengan Demonstrasi Terhadap Kompetensi Mahasiswa Keperawatan Dalam Melakukan Skills Tracheostomy Care Di Universitas Muhammadiyah Surakarta - Setianingsih, Fitri Andriani, Enita dewi, S.Kep., Ns., MN (2017)
Background: Nurses are the health workers who play an important role in health care. Nurses are required to be competent for providing. These competencies can be initiated from high-quality educational institutions. In order to achieve professional skills in providing health services required a conducive teaching and learning process that can be seen at the curriculum, faculty, infrastructure and learning methods. The method used in a series of learning system plays an important role. The methods required in the learning process include video tutorials, simulations, and demonstrations. Good learning strategy is needed in skills lab to minimize the gap between reading and clinical setting. The purpose of this study was to determine differences in video tutorials with simulations and a demonstration of the competence of nursing students in performing a tracheostomy care skills. Methods: This study used quantitative descriptive analysis retrospective design. The sample used in this study is 73 students of 2012 intake that followed the OSCA with the method of demonstration and 83 students of 2013 intake who undertaken the OSCA. The sampling technique used purposive sampling. The instrument used is the value of OSCA students who have not in remedial. The analysis used it this research is univariate and bivariate analysis. Results: Students are given a demonstration has an average value of OSCA tracheostomy care as much (76.14) with a standard deviation (12,160). While students are given video tutorials and simulation as much as the average value (67.86) with a standard deviation (11,770). Based on Independent Samples Test t test showed that p-value less than 0.05. Conclusion: There is significant difference to the competence of tracheostomy care skills between the two groups. Students with an average demonstration method value is higher than the video tutorials and simulations. Suggestions in this research is demonstration can be contined with video tutorial and simulation for better understanding in integrative nursing care.